Estimation of Groundwater recharge by groundwater level fluctuation method of Dibdibba aquifer at ‎Karbala- Najaf plateau, central of Iraq - Al-Kubaisi, Qusai Y.; Al-Abadi, Alaa M.; Al-Ghanimy, Maitham A. (Iraqi Journal of Science, 2018)
Groundwater recharge estimation is essential for management of groundwater systems. As groundwater is a vital source of water for domestic and agricultural activities in the study area (Karbala - Najaf plateau), ‎where the Dibdibba aquifer represents the primary and essential aquifer, evaluation of groundwater recharge is critical in the study area. A wide range of methodologies exists for estimating recharge.‎ ‎The water-table fluctuation method strategy might be the most generally utilized system for estimating recharge; it requires learning of changes in water levels over time and specific yield. Advantages of this approach include its simplicity and an insensitivity to the mechanism by which water moves through the unsaturated zone. Sensitiveness in measures created by this technique relates to the compelled precision with which ‎specific yield can be calculated and to the degree to which assumptions inherent in the strategy are ‎valid. The primary objective of this study is to calculate the annual and monthly ‎values of recharge for Jan. 2010 ‎through Aug. ‎‎2017‎ for Dibdibba aquifer at Karbala - Najaf plateau, central of Iraq to use results in the management of groundwater in the study area later‎. ‎Water levels measured in four observation wells in the study area, measurements were taken daily at the ‎middle of the night automatically by using modern electronic devices installed on the wells (from 10 BM to 4 AM) to avoid the effect of pumping ‎activity on the water ‎levels and to neutralize the effect of evapotranspiration for Jan. 2010 to Aug. 2017‎.